An analytic algorithm to calculate the inclination, ascending node, and semimajor axis of spectroscopic binary orbits using a single speckle measurement and the parallax - Docobo, Jose Angel; Campo, P P; Andrade, Manuel; Horch, Elliott P (Astrophysical Bulletin, 2014)
It is well known that in spectroscopic binary orbits, the inclination, the ascending node, and the semimajor axis remain undetermined, therefore the principal objective of this research is to establish an analytic methodology for the calculation of these parameters for spectroscopic binaries, both single-lined (SB1) and double-lined (SB2). In other words, the goal is to determine their “three-dimensional” orbits using a single speckle measurement (ρ, θ, t) and the parallax (π). Moreover, estimates of the individual masses of each system can also be obtained. The proposed algorithm was successfully applied to SB1 systems: YSC 148 (HD 37393) and CHR 225 (HD 34318), and SB2 systems: LSC 1 Aa1,2 (HD 200077) and Mkt 11 Aa, Ab (HD 358). In this late case, previously determined spectroscopic and visual orbits have been used to compare and contrast the results obtained from them with our results. The methodology presented is especially interesting for those cases in which it is only possible to resolve the spectroscopic binary in the zones of maximum angular separation by optical means thereby making it impossible to avail of sufficient observations in order to calculate the visual orbit. © Pleiades Publishing, Ltd. 2014.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-814-675-311-054 tex.type: [object Object]
Keywords: dept.phy; general; high angular resolution—techniques; interferometric—binaries; techniques

Orbits of 14 binaries based on 2018 SOAR speckle observations - Docobo, José A; Gomez, Jorge; Campo, Pedro P; Andrade, Manuel; Horch, Elliott P; Costa, Edgardo; Mendez, Rene A (Monthly Notices of the Royal Astronomical Society, 2019)
New data obtained during the 2018 March-April speckle run at the 4.1 m Southern Astrophysical Research (SOAR) telescope located at Cerro Pachón (Chile) allowed us to recalculate the orbits of the following visual binaries: WDS 06478+0020 (STT 157),WDS 07003-2207 (FIN 334Aa,Ab), WDS 07013-0906 (A 671), WDS 10174-5354 (CVN 16Aa,Ab), WDS 12155-3106 (RST 1658),WDS 12572+0818 (FIN 380),WDS 13044-1316 (HU 642),WDS 14243-3838 (RST 1785), WDS 16094-3103 (I 557), WDS 17115-1630 (HU 169), WDS 17119-0151 (LPM 629),WDS 17563 + 0259 (A 2189),WDS 18464-2755 (RST 2073), and WDS 19035-6845 (FIN 357). All but three of them are Southern stars. The recently published Gaia parallaxes were used to calculate the total mass of each of these systems, despite the fact that, in a few cases, only Hipparcos parallaxes were available. For two binaries, A 671 and RST 2073, there are no parallax data. However, in these cases, the masses deduced from the dynamical parallaxes provided relevant information. In addition, we also present the first orbit for each of three systems: HU 642, RST 1785, and RST 2073, using speckle measurements. Finally, using the dynamical parallaxes given by these orbits, we have been able to calculate the luminosity of these systems. Said luminosities allow us to indicate an approximate age for each of the components of the system, situating them within the HR diagram. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-727-074-773-961, pop00143 tex.type: [object Object]
Keywords: Techniques: high angular resolution - astrometry - binaries; Visual - stars: fundamental parameters; dept.phy; peer-reviewed